2019
DOI: 10.1038/s41467-019-12732-2
|View full text |Cite
|
Sign up to set email alerts
|

Resident memory T cells are a cellular reservoir for HIV in the cervical mucosa

Abstract: HIV viral reservoirs are established very early during infection. Resident memory T cells (TRM) are present in tissues such as the lower female genital tract, but the contribution of this subset of cells to the pathogenesis and persistence of HIV remains unclear. Here, we show that cervical CD4+TRM display a unique repertoire of clusters of differentiation, with enrichment of several molecules associated with HIV infection susceptibility, longevity and self-renewing capacities. These protein profiles are enric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(97 citation statements)
references
References 68 publications
1
82
0
Order By: Relevance
“…Very recently, resident memory CD4 + T cells (T RM ), present in tissues such as the lower female genital tract has been described as a critical HIV-1 reservoir in cervical mucosa (Cantero-Pérez et al, 2019). Interestingly, cervical tissues from aviremic ARTtreated HIV-1 infected woman contained higher viral DNA content compared to blood samples and showed that CD4 + T RM harboring viral DNA and viral RNA are the main contributors to this reservoir.…”
Section: Cd4 + T Cell Functional Subsetsmentioning
confidence: 99%
“…Very recently, resident memory CD4 + T cells (T RM ), present in tissues such as the lower female genital tract has been described as a critical HIV-1 reservoir in cervical mucosa (Cantero-Pérez et al, 2019). Interestingly, cervical tissues from aviremic ARTtreated HIV-1 infected woman contained higher viral DNA content compared to blood samples and showed that CD4 + T RM harboring viral DNA and viral RNA are the main contributors to this reservoir.…”
Section: Cd4 + T Cell Functional Subsetsmentioning
confidence: 99%
“…Therefore, identification of mechanisms which promote the generation and retention of CD4 + T RM should be further explored for development of more effective vaccines against a range of human pathogens [130]. Of note, female lower genital tract CD4 + T RM were identified to serve as primary targets of HIV infection and persistence, thus providing an HIV cellular sanctuary [131]. Thus, HIV treatment strategies and vaccines may consider targeting T RM [131].…”
Section: Cd4 + T Rm Subset Functionmentioning
confidence: 99%
“…Of note, female lower genital tract CD4 + T RM were identified to serve as primary targets of HIV infection and persistence, thus providing an HIV cellular sanctuary [131]. Thus, HIV treatment strategies and vaccines may consider targeting T RM [131].…”
Section: Cd4 + T Rm Subset Functionmentioning
confidence: 99%
“…High-dimensional distance calculations revealed that kNN latent cells were more similar between lymph node and gut than between the tissues and blood, suggesting phenotypic commonalities in the latent reservoir found in tissues. Indeed, kNN latent cells from both lymph node and gut expressed high levels of the Trm marker CD69, suggesting that Trm in these tissues, like those from the cervix (Cantero-Perez et al, 2019), preferentially harbor the reservoir. Together with our observation that kNN latent cells from all sites examined expressed high levels of PD1, these results suggest PD1-expressing Trm as possible targets to eliminate the tissue reservoir.…”
Section: Discussionmentioning
confidence: 99%
“…Several antigens distinguished kNN latent cells in blood vs. tissues. For instance, CD27, an antigen expressed on Tcm cells, and CD69, a marker of activation in blood but a T resident memory (Trm) marker in tissues (Cantero-Perez et al, 2019), were more highly expressed on FNA kNN latent cells ( Fig. 4D, S7A).…”
Section: Phenotypic Features Of Tissue Knn Latent Cellsmentioning
confidence: 99%